Metabolic changes of Interleukin-12/15/18-stimulated human NK cells - Iñigo Terrén (Nature Portfolio, 2021)
Abstract Natural Killer (NK) cells acquire memory-like properties following a brief stimulation with IL-12, IL-15 and IL-18. These IL-12/15/18-preactivated NK cells, also known as cytokine-induced memory-like (CIML) NK cells, have been revealed as a powerful tool in cancer immunotherapy due to their persistence in the host and their increased effector functions. Several studies have shown that NK cells modulate their metabolism in response to cytokine-stimulation and other stimuli, suggesting that there is a link between metabolism and cellular functions. In this paper, we have analyzed metabolic changes associated to IL-12/15/18-stimulation and the relevance of glycolytic pathway for NK cell effector functions. We have found CIML NK cells are able to retain a metabolic profile shifted towards glycolysis seven days after cytokine withdrawal. Furthermore, we found that treatment with 2-DG differently affects distinct NK cell effector functions and is stimuli-dependent. These findings may have implications in the design of NK cell-based cancer immunotherapies.